2022
DOI: 10.1038/s41550-022-01641-y
|View full text |Cite
|
Sign up to set email alerts
|

A low-eccentricity migration pathway for a 13-h-period Earth analogue in a four-planet system

Abstract: OI-500 (also known as HIP 34269, TIC 134200185 and CD-47 2804) is a high-proper-motion star (Table 1) with a radial velocity of 55.6 km s −1 (ref. 1 ) and a V-band magnitude of 10. 54 (ref. 2 ) located at a distance of 47.39 pc from the Sun 1 . The National Aeronautics and Space Administration's (NASA's) Transiting Exoplanet Survey Satellite 3 (TESS) observed TOI-500 for the first time in sectors 6, 7 and 8 between 11 December 2018 and 28 February 2019. The TESS Science Processing Operations Center 4 (SPOC) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 151 publications
0
6
0
Order By: Relevance
“…In these models, planet migration occurs after the dissipation of the protoplanetary disk, by a combination of eccentricity forcing from the planetary companions and tidal dissipation in the innermost planet's interior, although the precise dynamical forcing mechanisms are debated. Serrano et al (2022) showed, for TOI-500, that the low-eccentricity secular forcing proposed by Pu & Lai (2019) can explain the migration of that system's USP planet from a formation radius of ∼0.02 au to its observed location. For GJ 367 b, we tested this migration scenario with similar initial conditions (USP planet starting at 0.02 au, initial eccentricities of all planets set to 0.2), and found only modest migration of planet b, from 0.02 au to ∼0.01 au, short of the observed 0.007 au.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In these models, planet migration occurs after the dissipation of the protoplanetary disk, by a combination of eccentricity forcing from the planetary companions and tidal dissipation in the innermost planet's interior, although the precise dynamical forcing mechanisms are debated. Serrano et al (2022) showed, for TOI-500, that the low-eccentricity secular forcing proposed by Pu & Lai (2019) can explain the migration of that system's USP planet from a formation radius of ∼0.02 au to its observed location. For GJ 367 b, we tested this migration scenario with similar initial conditions (USP planet starting at 0.02 au, initial eccentricities of all planets set to 0.2), and found only modest migration of planet b, from 0.02 au to ∼0.01 au, short of the observed 0.007 au.…”
Section: Discussionmentioning
confidence: 94%
“…The formation process of USP planets is still not fully understood, and different scenarios have been proposed to explain their short-period orbits: dynamical interactions in multiplanet systems (Schlaufman et al 2010); low-eccentricity migration due to secular planet-planet interactions (Pu & Lai 2019); high-eccentricity migration due to secular dynamical chaos (Petrovich et al 2019); tidal orbital decay of USP planets formed in situ (Lee & Chiang 2017); and obliquity-driven tidal migration (Millholland & Spalding 2020). Intensive follow-up observations of systems hosting USP planets can help us to understand the formation and evolution mechanisms of shortperiod objects and other phenomena related to star-planet interactions (Serrano et al 2022). Sanchis-Ojeda et al (2014), Adams et al (2017), andWinn et al (2018) found that most USP planets have nearby planetary companions.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a second planet candidate motivates us to collect additional RV data for this system in order to determine the period and measure the mass of the second planet candidate while also improving the uncertainty on the mass measurement of TOI-1075 b. Additionally, there are currently a handful of systems consisting of a USP planet and a close-in companion with periods ranging from a few days to tens of days, e.g., K2-106 (Guenther et al 2017), K2-141 (Malavolta et al 2018), K2-229 (Santerne et al 2018, and TOI-500 (Serrano et al 2022). These close-in companions could be responsible for migrating the USP planets to their current positions (Pu & Lai 2019;Millholland & Spalding 2020;Serrano et al 2022). The possible existence of such a close-in companion in the TOI-1075 system serves as additional motivation for further RV follow-up of the system.…”
Section: A Potential Second Planet In the Systemmentioning
confidence: 99%
“…Within our planet sample, TOI-561 b, CoRoT-7 b, and TOI-500 b have the lowest bulk densities with densities of 3.00 ± 0.80 g cm −3 , 5 ± 1.5 g cm −3 , and -+ -4.9 g cm 0.88 1.03 3 , respectively (Léger et al 2011;Lacedelli et al 2021;Serrano et al 2022). However, we find that the lowest bulk density produced by our models for the same planet mass is only consistent with the measurements for TOI-500 b.…”
Section: Lowest-density Planet Producedmentioning
confidence: 78%